1996
DOI: 10.1016/s0002-9343(96)00014-9
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial Staphylococcus aureus bacteremia among nasal carriers of methicillin-resistant and methicillin-susceptible strains

Abstract: Among ICU patients, nasal carriers of S aureus are at higher risk for S aureus bacteremia than are noncarriers; in the setting of an MRSA outbreak, colonization by methicillin-resistant strains represents a greater risk than does colonization by MSSA and strongly predicts the occurrence of MRSA bacteremia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
135
1
8

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(148 citation statements)
references
References 34 publications
4
135
1
8
Order By: Relevance
“…Furthermore, in the intervention and postintervention groups respectively, 22.0% and 26.9% of patients were found to have become positive in the first week of admittance to the ICU, which shows the high risk of nasal MRSA acquisition in an endemic situation. MRSA nasal carriers rates rang from 5.6% to 12.9% in ICU patients [5,10,23], such rates being lower than the ones found in our study. As yet, little is known about the MRSA nasal carrier epidemiology in ICU patients or its subsequent clinical consequences, since few in-depth investigations have been made.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…Furthermore, in the intervention and postintervention groups respectively, 22.0% and 26.9% of patients were found to have become positive in the first week of admittance to the ICU, which shows the high risk of nasal MRSA acquisition in an endemic situation. MRSA nasal carriers rates rang from 5.6% to 12.9% in ICU patients [5,10,23], such rates being lower than the ones found in our study. As yet, little is known about the MRSA nasal carrier epidemiology in ICU patients or its subsequent clinical consequences, since few in-depth investigations have been made.…”
Section: Discussioncontrasting
confidence: 90%
“…Pujol et al, in an ICU study, concluded that S. aureus nasal carriers are at a high risk for the development of bacteremia by the microorganism and suggest that treatment of those patients may be effective in controlling the agent [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10] Importantly, MRSA carriage is associated with a fourfold increased infection risk compared with MSSA colonization. 11,12 Many studies have evaluated the risk factors for nosocomial MRSA acquisition (eg, comorbidities, exogenous factors, and antimicrobial exposure) to improve preventive measures, [13][14][15] but despite 50 years of research, less is known about the protective factors at the host level. It has been hypothesized that endogenous MSSA carriage may protect against exogenous MRSA acquisition by competing for colonization of the anterior nares.…”
Section: Does Colonization With Methicillin-susceptiblementioning
confidence: 99%
“…Approximately 20% of all patients undergoing surgery acquires at least one nosocomial infection (15,10). It has been estimated that nasal carriers of S. aureus are most at risk to develop nosocomial infections, especially if seropositives, cirrhotic, dialysised (haemo-and peritoneal dialysis), liver grafted hospitalized in surgery and intensive care units (14,8). Infected and colonized patients are the reservoir of MRSA, and the main way of transmission from patient to patient is represented by health care workers.…”
Section: Introductionmentioning
confidence: 99%